LINGUO-CULTURAL ANALYSE OF PROVERBS WHICH EXPRESS GENDER IN ENGLISH, RUSSIAN AND UZBEK - Abdullayeva Munojot Mukhtorovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article the proverbs are given which express gender terms in the English, the Russian and the Uzbek languages. Linguo-cultural meanings are analysed by proverbs of the nationalities.